Evaluation of the 1958-59 Rabi Crop Campaign in Punjab, Rajasthan & U.P. - Planning Commission (Planning Commission, 1960)
Reviewing the food situation with his cabinet colleagues on the eve of the rabi season, 1958-59, the Prime Minister urged that a food production drive should be taken up during the season. The Minister for Food and Agriculture, acting on the suggestion, initiated the Rabi Crop Campaign on August 5,1958. He wrote to the Chief Ministers of the States that substantially higher yields were reported during the crop competitions, and if everything possible was done by the Government, enough could be done to boost up production even in the face of possible natural calamities. Among the programmes to be stressed under the campaign, he emphasized the building up of an efficient organisation at all levels, the coordination of the departmental arrangements for timely supply of seeds, manures, improved implements, etc., and the mobilisation of cultivators.
Government of India
Government of India